2017
DOI: 10.1016/j.neurobiolaging.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

The biomarker-based diagnosis of Alzheimer's disease. 1—ethical and societal issues

Abstract: There is great interest in the use of biomarkers to assist in the timely identification of Alzheimer's disease (AD) in individuals with mild symptoms. However, the inclusion of AD biomarkers in clinical criteria poses socioethical challenges. The Geneva Task Force for the Roadmap of Alzheimer's Biomarkers was established to deliver a systematic strategic research agenda (aka roadmap) to promote efficient and effective validation of AD biomarkers and to foster their uptake in clinical practice. In this article,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(104 citation statements)
references
References 45 publications
0
104
0
Order By: Relevance
“…, Lock , Porteri et al . ). Second, attention has been drawn to the possible harm caused by communicating biomarker test results associated with the risk of developing the common late‐onset, sporadic form of Alzheimer's dementia when no effective treatments are available (Fox et al .…”
Section: Communicating Test Results Related To Alzheimer's Disease Riskmentioning
confidence: 97%
See 1 more Smart Citation
“…, Lock , Porteri et al . ). Second, attention has been drawn to the possible harm caused by communicating biomarker test results associated with the risk of developing the common late‐onset, sporadic form of Alzheimer's dementia when no effective treatments are available (Fox et al .…”
Section: Communicating Test Results Related To Alzheimer's Disease Riskmentioning
confidence: 97%
“…The focus on identifying and intervening at earlier stages of pathological processes thought to be associated with dementia has prompted concerns on two fronts. First, given the ambiguity of the Alzheimer's label, the prognostic and diagnostic content conveyed by biomarker results is inevitably vague (Boenink et al 2016, Lock 2013, Porteri et al 2017. Second, attention has been drawn to the possible harm caused by communicating biomarker test results associated with the risk of developing the common late-onset, sporadic form of Alzheimer's dementia when no effective treatments are available (Fox et al 2013, Karlawish 2011, Molinuevo, Cami et al 2016, Schicktanz et al 2014.…”
Section: Communicating Test Results Related To Alzheimer's Disease Riskmentioning
confidence: 99%
“…Moreover, even in the absence of disease modifying drugs, the advantages of an accurate diagnosis justify the use of (relatively) advanced diagnostic technology. 55 Knowing the aetiology of an individual's cognitive impairment before the dementia stage already allows for the delivery of timely and appropriate personalized care, including appropriate counselling and future planning, preventing the use of inappropriate medications and ancillary investigations, taking eventually appropriate steps to prevent unsafe behaviours (e.g., driving), allowing access to currently available symptomatic drugs, 55 and recruitment to research and clinical trials. In Europe and the US less than 50% of people with clinical dementia receive a formal diagnosis of dementia in primary care.…”
Section: 6mentioning
confidence: 99%
“…55,57,[59][60][61][62][63][64] Briefly, literature reviews were performed using harmonized strings for all individual aims of the 5 phases (Supplementary Table). The core data are reported in Panel 5 and briefly summarized below.…”
Section: Research Priorities For Ad Biomarker Validation To Launch Phmentioning
confidence: 99%
“…Considerations include the knowledge of personal likelihood of developing dementia in the future (hypothetically or based on biomarkers), assessment of the significance of that risk, the likelihood of unwanted side‐effects of preventative treatment being tested and assessment of the significance of side‐effects. The ethical and societal issues raised by the uncertainty of prognostic information based on biomarker test results are being considered . A survey which included people with no cognitive impairment, people with mild cognitive impairment and people with a diagnosis of dementia, found that trials enrolling pre‐dementia populations may face challenges in enrolment, especially where frequent visits and biomarker testing are required.…”
Section: Introductionmentioning
confidence: 99%